Treatment of Tuberculous Meningitis and Its Complications in Adults - Bharat Lal, Awais Bashir, Sikandar-e-Aram, Naseer Memon, Hamad Akbar Shaikh, Abdul Rashid Baloch (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To determine the frequency of complications of Tuberculous Meningitis and review its treatment. Methods: This cross sectional study was conducted in the department of medicine unit-III, PMC’ Hospital Nawabshah from January 2016 to December 2016, on 122 patients who were admitted with complaints of headache, fever, neck stiffness or unconsciousness were studied. After taking history and examination, the baseline investigations were sent along with x-ray chest, contrast CT Brain was done where needed. After fundoscopy and imaging Lumber Puncture was done and CSF was sent for detailed examination. Diagnosis of tuberculous meningitis was made on 32 cases by presence of mycobacteria in CSF by Staining and 1 or Culture or clinical meningitis with headache, fever, CSF showing increased protein, decreased glucose, and pleocytosis with Lymphocyte predominance and response to anti tuberculous drugs. Patients were examined daily. If patients developed new complication then CT or MRI brain was repeated. Result: 32 patients with tuberculous meningitis were identified. More than half of the cases were presented with one or more complications. Hydrocephalus was found in 8.7 %, stroke in 15.6 %, cranial nerve palsy in 21.8 %, visual impairment in 9.3 %, seizure in 18.6 % and death occurred in 18.7 %. Conclusion: Tuberculous meningitis is associated with significant risk of complication and death.